Dermatoses in rowers - Mokha, M.; Hauck, S. (International Journal of Athletic Therapy & Training, 2014)
The article offers brief description of specific causes of dermatoses in athletes which have been categorized as mechanical, environmental, and infectious causes. Topics discussed include mechanical causes such as blisters, environmental causes such as sunburn, and infectious causes such as acne mechanica. Also provided is the information on their clinical presentation and various treatments available.